Gold(I) catalyzed [1,3] O -> C rearrangement of benzylvinyl ethers - Kona, Chandrababu Naidu; Patil, Mahesh N.; Ramana, Chepuri V. (Organic Chemistry Frontiers, 2016)
A simple procedure for the preparation of 3-(hetero) arylpropionaldehydes has been developed employing a gold-catalyzed [1,3]-rearrangement of vinyl ethers. Using this protocol, Canthoxal, an aromatic aldehyde used in perfumery, has been prepared on a gram scale.